PENGUKURAN MEDAN MAGNETIK BATUAN MENGGUNAKAN SENSOR FLUXGATE - Airin Ahad Dini (Department of Physics – Universitas Negeri Padang UNP, 2013)
Magnetic minerals serve as the main support technology. To know the content of a substance requires magnetic sensors. One type of sensor for detecting a magnetic field is fluxgate sensor, which works based on changes in magnetic flux surrounding the sensor element. This research plan of measuring tools based rock magnetic field fluxgate sensor. The purpose of this study was explained performansi specification of measurment instruments, determining the accuracy and precision of measurements, measuring tools fluxgate magnetic field sensor based. This research is a research laboratory experiment. Measurement techniques and data collection is performed directly and indirectly. Direct measurements carried out on the magnetic field strength of different rocks and see the effects on the output voltage produced by the magnetic field measuring devices. While the collection and measurement is kelinieran indirectly to the magnetic field and the bias magnetic field strength measuring devices. Data obtained through measurement is analyzed in two ways, namely in statistics and graphics. Based on the analysis performed can be explained several important results. First,measurement instrument of magnetic field based on fluxgate sensor consists of three elements namely the fluxgate sensor and the signal processing chain. Second, the closer the distance measurement on the sensor samples the value shown will improve. Third, the design specifications of the magnetic field measuring devices based fluxgate sensor is in the form of precision and accuracy of a measuring instrument. Having obtained the accuracy of measurement of the magnetic field and the precision 0.986,0.972. Measurment instrument has a precision and accuracy are high enough on the magnetic field. Keyword : Fluxgate sensor, magnetic field, sensitivity, accuracy, precision.